PELAYANAN PERIZINAN ONLINE SINGLE SUBMISSION (OSS) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN PELALAWAN TAHUN 2022 - Amanda, Yayan; Tinov, M.Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The Pelalawan Regency One-Stop Integrated Service and Investment Service has implemented the Online Single Submission (OSS) policy. The aim of this research is to determine the quality of Online Single Submission (OSS) licensing services at the Pelalawan Regency Investment and One Stop Integrated Services Service. The theory used in this research is about the Quality of Public Services with indicators of Direct Evidence, Reliability, Responsiveness, Assurance, Empathy. The type of research used is qualitative descriptive research. The data sources used are primary data and secondary data. The informants in this research were the Pelalawan Regency Investment and One-Stop Integrated Services Service, employees and also the community who received services. Data collection techniques using in-depth interviews and documentation. From the research results, it can be stated that the quality of Online Single Submission (OSS) licensing services at the Pelalawan Regency One Stop Investment and Integrated Services Service is not yet good due to several obstacles such as: Process and access to services that are still very poor, Standard Operating Procedures that are not yet clear and errors occur in Online Single Submission (OSS) which hampers the data collection process due to verification and notification via Online Single Submission (OSS). The constraint factor for the Online Single Submission (OSS) service is the lack of socialization provided to the public. This means that there are still many people who do not understand or know about the Online Single Submission (OSS) service procedures so that people still have to come to the One Stop Investment and Integrated Services Office. to find out about the use of Online Single Submission (OSS). Keywords : Quality, Service, Online Single Submission (OSS)